2020
DOI: 10.1002/path.5510
|View full text |Cite
|
Sign up to set email alerts
|

The choroid plexus stroma constitutes a sanctuary for paediatric B‐cell precursor acute lymphoblastic leukaemia in the central nervous system

Abstract: Despite current central nervous system‐directed therapies for childhood B‐cell precursor acute lymphoblastic leukaemia, relapse at this anatomical site still remains a challenging issue. Few reports have addressed the study of the specific cellular microenvironments which can promote the survival, quiescence, and therefore chemoresistance of B‐cell precursor acute lymphoblastic leukaemia cells in the central nervous system. Herein, we showed by immunofluorescence and electron microscopy that in xenotransplante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Moreover, co-culture with choroid plexus fibroblasts protected the leukaemic cells when exposed to methotrexate or cytarabine, drugs commonly used in treating CNS leukaemia in infant and paediatric patients. Overall, these findings suggest that the choroid plexus, specifically the fibroblasts within this structure, forms part of the CNS leukaemia niche and is important in facilitating leukaemia cell survival at this site ( Fernández-Sevilla et al, 2020 ). In particular, the study scratches the surface of two important considerations.…”
Section: Aspects Of Niche Involvement In Infant Leukaemiamentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, co-culture with choroid plexus fibroblasts protected the leukaemic cells when exposed to methotrexate or cytarabine, drugs commonly used in treating CNS leukaemia in infant and paediatric patients. Overall, these findings suggest that the choroid plexus, specifically the fibroblasts within this structure, forms part of the CNS leukaemia niche and is important in facilitating leukaemia cell survival at this site ( Fernández-Sevilla et al, 2020 ). In particular, the study scratches the surface of two important considerations.…”
Section: Aspects Of Niche Involvement In Infant Leukaemiamentioning
confidence: 95%
“…The choroid plexus is responsible for CSF production and a key element of the blood-CSF barrier. Fernández-Sevilla et al recently showed that ALL cells infiltrate the choroid plexus in a murine xenograft model ( Fernández-Sevilla et al, 2020 ). They demonstrated that B-cell precursor ALL cells and human choroid plexus fibroblasts interact in vitro , mediated by reciprocal expression of adhesion molecules, and that choroid plexus fibroblasts acquire a cancer-associated fibroblast phenotype.…”
Section: Aspects Of Niche Involvement In Infant Leukaemiamentioning
confidence: 99%
“…On the other hand, the treatment with GSI-XII, DAPT, and the blocking antibody against Notch4 in B-ALL potentiated the anti-viability and pro-apoptotic effects of cytarabine in an ROS-dependent way. In addition, the co-administration of GSI-XII and cytarabine lowered the bone marrow leukemic burden in a murine xenograft model of B-ALL [564], while DAPT reduced central nervous system infiltration in a B-ALL murine model and led to increased chemosensitivity of leukemic cells to Ara-C by impairing their interaction with choroid plexus stroma expressing high levels of Jagged1 and ADAM10 [565].…”
Section: Cytarabinementioning
confidence: 99%
“…Importantly, disruption of the meningeal ALL adhesion with tMe6TREN ethyl]amine) increased the efficacy of chemotherapy in the CNS in leukemia xenograft murine models (Jonart et al, 2020). Other studies demonstrated that B-ALL cells from children and B-ALL cell lines were adherent to astrocytes, choroid plexus fibroblasts, and epithelial cells, thus promoting leukemic cell survival and chemoresistance (Akers et al, 2011;Fernández-Sevilla et al, 2020).…”
Section: Cell Adhesion In Leukemic Cell Colonization Of the Central Nervous Systemmentioning
confidence: 99%